Strategi Penjualan dalam Meningkatkan Pendapatan Pedagang Pakaian di Pasar Sentral Kota Gorontalo - Nusu, Fadlia; Gobel, Lisda Van; Gintulangi, Sabriana Oktaviana (Ideas: Jurnal Pendidikan, Sosial dan Budaya, 2025)
This study aims to identify the sales strategies employed by lingerie traders to increase income in the Central Market of Gorontalo City. The research method used is descriptive qualitative with data collection techniques through observation, interviews, and documentation. The informants consist of traders, consumers, and related institutions. The results show that the majority of traders have not optimally utilized digital technology, have conducted insufficient periodic inspections of goods, and have not established effective communication with consumers. This has resulted in a decline in income and competitiveness of traders amidst the development of the digital market. This study recommends the need for digital marketing training and customer service approaches as strategies to increase income.